Determination Yield To Maturity Bonds, Audit Quality As Moderators - Deri Yanto; Darmansyah Darmansyah (LPPM Universitas BSI, 2021)
Yield to maturity bonds are often used by investors in the effort to obtain mutual returns from investments and reduce the mismatch of the acquisition value obtained. Several factors that influence it such as exchange rates, inflation, BI interest rates, debt to equity ratio, and company size are also to examine the effect of audit quality in moderating the relationship. The purpose of this study was to determine how the influence of exchange rates, inflation, BI interest rates, debt to equity ratio, and company size also when moderated by audit quality. Audit quality as a moderator is taken as a means of increasing public trust, especially investors. The research sample is corporate companies that issued bonds on the Indonesia Stock Exchange in 2014 - 2018, as many as 103 companies with emissions that met the research requirements of 110 emissions. The method used is purposive sampling and multiple linear regression techniques. The results showed a correlation between the rate of return with yield to maturity, there were 3 significant influences namely the exchange rate moderated by audit quality, company size and company size moderated by audit quality. This research model based on the determinant test results was able to explain the dependent variable by 55.9% while 44.1% was explained by other dependent variables by 55.9% while 44.1% was explained by other variables.Keywords: Exchange Rate, BI Rate, Debt to Equity Ratio, Size, and Yield to Maturity Bonds.